Comparative animal study of the antinociceptive efficacy of lamotrigine and gabapentin for the management of pain - Szabo, Akos; Bocsan, I. C.; Suciu, S.; Buzoianu, A. D. (Acta physiologica Hungarica, 2015)
Pain relief using drugs with high efficacy provides significant improvement in the patients’ lives. Drugs like lamotrigine (LTG) and gabapentin (GBP) have the ability to overcome the symptoms of neuropathic pain. Aim: The present study offers a comparative analysis of LTG and GBP efficacy in a rat model of nociceptive pain after single administration. Method: Sixty-three Wistar-Bratislava rats randomized into 7 groups were included: a control group treated with saline solution and 6 groups treated with different doses of LTG and GBP. Nociceptive responses to thermal and mechanical stimulations were evaluated before and after drug administration, at different time intervals, using paw pressure and hot plate tests. The obtained data were statistically analyzed, with significance at p value < 0.05. Results: LTG 100 mg/kg and 50 mg/kg presented a significant analgesic effect in both mechanical and thermal tests, 1 and 2 hours after administration. GBP 100 mg/kg increased latency time in hot plate test. The effect of both anticonvulsant drugs occurred rapidly after administration, but had a short duration. Conclusions: LTG and GBP had an analgesic effect in a single dose administration. The effect of LTG was more evident since it was observed in both tests. Their effect was dose dependent.